Energy-efficient data dissemination and data gathering in wireless environments - Yao, Yuxia (2010)
Advances in wireless communication technology and portable devices have made data dissemination and gathering increasingly popular over wireless networks. In this thesis, we investigate energy-efficient data dissemination and data gat hering in wireless environments. Data broadcast has been recognized as an important method of wireless data dissemination. In the first part of the thesis, we investigate energy-efficient indexing techniques for push-based data broadcast. To cater for energy efficiency, existing air indexing schemes for data broadcast have focused on reducing tuning time only, i.e., the duration that a mobile client stays active in data accesses. On the other hand, existing broadcast scheduling schemes have aimed at reducing access latency through non-flat data broadcast to improve responsiveness only. Not much work has addressed the energy efficiency and responsiveness issues concurrently. We propose an energy-efficient indexing scheme called MHash that optimizes tuning time and access latency in an integrated fashion. MHash reduces tuning time by means of hash-based index and supports non-flat data broadcast to reduce access latency. The design of hash function and the optimization of bandwidth allocation are investigated in depth to refine MHash. Experimental results show that under non-uniform access distribution, MHash out performs st ate-of-the-art air indexing schemes in energy efficiency and achieves access latency close to optimal broadcast scheduling.